The future of the ban on biological weapons - Oliver Thränert; Sascha Lange (Stiftung Wissenschaft und Politik (SWP), 2006)
The treaty members of the Biological Weapons Convention (BWC) will meet for the sixth review conference from November 20 to December 8, 2006. Since the United States will not take the lead and most of the non-aligned states remain very sceptical of the Western dominated debate regarding the non-proliferation of ABC weapons, Germany and the European Union will play a central role at this conference.The BWC does not have any detailed inspection mechanisms. Negotiations dealing with an additional protocol, which should also include verification procedures, failed in 2001. This is even more unfortunate, since the rapid development of bio-scientific knowledge could make biological weapons even more dangerous in the future.What can be done in order to strengthen this treaty? Which other fields beyond the direct multilateral armament controls could prove meaningful in strengthening the ban on biological weapons? What sort of policy should be adopted?At the 2006 review conference, the adoption of a new working program for the member states will be important for the time period 2007-2011. The subject matter for this working program of the BWT should include the national implementation of activities, the revision of confidence-building measures as well as a discussion of the progress in bio-scientific knowledge and its consequences. Additionally, member states must specify on export controls, intensify prevention programs against biological weapons and promote a social consciousness regarding the dangers of abusing bio-scientific knowledge by means of conduct codes. (SWP-Research Papers)
Keywords: 320